Types Validity of Arbitration Agreement Under United Arab Emirates Law - Falaknaz, Sara Ali (2016)
The theme of this dissertation is a detailed study about the conditions required to validate any arbitration agreement under the United Arab Emirates Law. It deals with the basic characteristics and definitions of the arbitration agreement as well as how is it valid under the UAE law. This thesis will also discuss the advantages and the disadvantages of the arbitration in UAE. The paper also aims to present the types of the arbitration agreement in UAE and the requirements of each agreement to be valid as it will also examine the existing legislation and laws along with some Court of Cassations judgments. The paper will as well mention the rules of the several arbitration institutions in UAE regarding the different types of the arbitration agreement and their requirement. Any arbitration clause may be defective, as this paper will also state the different types of the defective arbitration clauses and how to avoid it by using standard arbitration clauses.